Impact of Tamoxifen on Vorinostat-Induced Human Immunodeficiency Virus Expression in Women on Antiretroviral Therapy: AIDS Clinical Trials Group A5366, The MOXIE Trial . (17th February 2022) - Scully, Eileen P; Aga, Evgenia; Tsibris, Athe; Archin, Nancie; Starr, Kate; Ma, Qing; Morse, Gene D; Squires, Kathleen E; Howell, Bonnie J; Wu, Guoxin; Hosey, Lara; Sieg, Scott F; et al.
Abstract: Background: Biological sex and the estrogen receptor alpha (ESR1) modulate human immunodeficiency virus (HIV) activity. Few women have enrolled in clinical trials of latency reversal agents (LRAs); their effectiveness in women is unknown. We hypothesized that ESR1 antagonism would augment induction of HIV expression by the LRA vorinostat. Methods: AIDS Clinical Trials Group A5366 enrolled 31 virologically suppressed, postmenopausal women on antiretroviral therapy. Participants were randomized 2:1 to receive tamoxifen (arm A, TAMOX/VOR) or observation (arm B, VOR) for 5 weeks followed by 2 doses of vorinostat. Primary end points were safety and the difference between arms in HIV RNA induction after vorinostat. Secondary analyses included histone 4 acetylation, HIV DNA, and plasma viremia by single copy assay (SCA). Results: No significant adverse events were attributed to study treatments. Tamoxifen did not enhance vorinostat-induced HIV transcription (between-arm ratio, 0.8; 95% confidence interval [CI], .2–2.4). Vorinostat-induced HIV transcription was higher in participants with increases in H4Ac (fold increase, 2.78; 95% CI, 1.34–5.79) vs those 9 who did not (fold increase, 1.04; 95% CI, .25–4.29). HIV DNA and SCA plasma viremia did not substantially change. Conclusions: Tamoxifen did not augment vorinostat-induced HIV RNA expression in postmenopausal women. The modest latency reversal activity of vorinostat, postmenopausal status, and low level of HIV RNA expression near the limits of quantification limited assessment of the impact of tamoxifen. This study is the first HIV cure trial done exclusively in women and establishes both the feasibility and necessity of investigating novel HIV cure strategies in women living with HIV. Clinical Trials Registration: NCT03382834. Abstract : Combination therapy with tamoxifen and vorinostat did not augment human immunodeficiency virus (HIV) latency reversal over vorinostat alone in post-menopausal women. Histone acetylation changes did associate with level of HIV RNA induction. Enrollment of women in interventional trials of cure strategies is feasible.